Factor structure of the professional quality of life scale among direct support professionals: factorial validity and scale reliability. Issue 9 (22nd July 2020) - Keesler, J. M.; Fukui, S.
Abstract: Background: Direct support professionals (DSPs) support people with intellectual and developmental disabilities in activities of daily living. DSPs may experience both contentment and struggles with their work. As agencies grapple with their recruitment and retention, understanding DSPs' holistic work experience is important. The Professional Quality of Life (ProQOL) scale assesses multiple domains of work experiences (i.e. compassion satisfaction, burnout and secondary traumatic stress). Despite extensive use across helping professions, the ProQOL is largely absent from DSP research. Method: This study examined the factor structure of the ProQOL with DSPs. Using secondary data from 495 DSPs, confirmatory factor analysis was conducted to determine if the original three‐factor structure holds for this population. Results: We confirmed the factorial validity of the ProQOL with the three‐factor solution. In the validation process, some modifications were suggested to the model, which also improved the scale reliability. Conclusions: The current study provides initial evidence of the factorial validity of the ProQOL when used with DSPs, as well as recommendations for subsequent improvements and future research.